A general equilibrium model with banks and default on loans - Tamon Takamura (Bank of Canada, 2013)
During the recent financial crisis in the U.S., banks reduced new business lending amidst concerns about borrowers' ability to repay. At the same time, firms facing higher borrowing costs alongside a worsening economic outlook reduced investment. To explain these aggregate business cycle patterns, I develop a model with households, banks and firms. I assume that a bank's ability to raise deposits is constrained by a limited commitment problem and that, furthermore, loans to firms involve default risk. In this environment, changes in loan rates affect the size of the business sector. I explore how banks influence the behavior of households and firms and find that both productivity and financial shocks lead to counter-cyclical default and interest rate spreads. I examine the implications of a government capital injection designed to mitigate the effect of negative productivity and financial shocks in the spirit of the Troubled Asset Relief Program (TARP). I find that the stabilizing effect of such policy interventions hinges on the source of the shock. In particular, a capital injection is less effective against aggregate productivity shocks because easing banks' lending stance only weakly stimulates firms' demand for loans when aggregate productivity falls. In contrast, a capital injection can counteract the adverse effect of financial shocks on the supply of loans. Finally, I measure aggregate productivity and financial shocks to evaluate the role of each in the business cycle. I find that the contribution of aggregate productivity shocks in aggregate output and investment is large until mid-2008. Financial shocks explain 65% of the fall in investment and 55% of the fall in output in the first quarter of 2009.
Keywords: E32; E44; E69; 330; Business fluctuations and cycles; Economic models; Financial stability